2018
DOI: 10.1111/bjh.15560
|View full text |Cite
|
Sign up to set email alerts
|

TP53 mutations are associated with mutated MYD88 and CXCR4, and confer an adverse outcome in Waldenström macroglobulinaemia

Abstract: Little is known about TP53 mutations in Waldenström Macroglobulinaemia (WM). We evaluated 265 WM patients for TP53 mutations by next-generation sequencing, and validated the findings by Sanger sequencing. TP53 mutations were identified and validated in 6 (2·6%) patients that impacted the DNA-binding domain. All six were MYD88- and CXCR4-mutated. Ibrutinib showed activity in patients carrying all three mutations. With a median follow-up of 18 months, 2 (33%) with biallelic TP53 inactivation died of progressive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
23
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 14 publications
3
23
1
Order By: Relevance
“…The sensitivity to induction of cell death was similar independently of TP53 mutational status. Very recently, Gustine et al have also reported 3 patients with TP53 mutation successfully treated with ibrutinib [45]. These data, consistent with observations in other lymphoid disorders, have to be confirmed in vivo with a large number of patients.…”
Section: Tp53 Alterations: Does It Influence Prognosis and Treatment supporting
confidence: 60%
See 1 more Smart Citation
“…The sensitivity to induction of cell death was similar independently of TP53 mutational status. Very recently, Gustine et al have also reported 3 patients with TP53 mutation successfully treated with ibrutinib [45]. These data, consistent with observations in other lymphoid disorders, have to be confirmed in vivo with a large number of patients.…”
Section: Tp53 Alterations: Does It Influence Prognosis and Treatment supporting
confidence: 60%
“…TP53 alterations (mutation, deletion, or uniparental disomy) presented a greater frequency of genomic aberrations compared with TP53 WT. Low frequency of TP53 mutation at diagnosis was confirmed by other groups [45,46]. Patients with TP53 alterations had a shorter overall survival and a shorter time to progression to a symptomatic disease.…”
Section: Tp53 Alterations: Does It Influence Prognosis and Treatment mentioning
confidence: 64%
“…33 Although TP53 mutations are uncommon in WM, they are present in MYD88-mutated patients. 32,34,35 Their association with poor outcome in MYD88-mutated patients has previously been reported. 34,35 Last, CXCR4 activating mutations found in 30% to 40% of MYD88 MUT patients were identified in MYD88 WT patients, although the frequency of these mutations was lower.…”
Section: %mentioning
confidence: 82%
“…Conventional chemo-immunotherapy is still indicated for most WM patients (Leblond et al, 2016) but recently, Poulain et al (2017) highlighted TP53 as a potential prognostic tool, indicating that TP53 independent therapy, would be the treatment of choice for WM patients harbouring TP53 variation. Gustine et al (2018) have also shown that TP53 mutations are associated with mutated MYD88 and CXCR4, and confer an adverse outcome in WM.…”
mentioning
confidence: 98%
“…Unlike Gustine et al (2018), two of the four patients with a TP53 variant were negative for MYD88 L265P and both these patients have become refractory to therapy with Bruton tyrosine kinase inhibitor (BTKi). One harbours a deleterious TP53 variant, which was detected prior to BTKi therapy, and is now responding to therapy with venetoclax (a BCL2 inhibitor); the other is the constitutional variant and is now stable post-chemoimmunotherapy.…”
mentioning
confidence: 99%